Kajian Kepemimpinan Transformasional, Komitmen Karyawan, Motivasi, Kepuasan Kerja, dan Kinerja Karyawan - Saptono, Edy (TRIKONOMIKA, 2014)
The research was conducted at BUMN Company of Defence Industry in West Java consists of the District and the city of PT Pindad, PT Dahana, PT Dirgantara Indonesia, PT LEN and PT Inti. The purpose of this study to determine, assess and analyze descriptive and verification of transformational leadership, employee commitment, motivation, job satisfaction and employee performance. Sample of this study using sampling technique cluster proporsional stratified random sampling. Methods of data collection using questionnaries. This research method using descriptive and verivicative with analysis technique of Structural Equation Modelling (SEM). Results from descriptive studies prove that transformational leadership rating of effective categories, employee commitment rating of strong categories, motivation rating of high categories, job satisfaction rating of satisfied categories and employee performance rating of high categories, but there are still some emploies who rate not good perception. The results of the verivication studies prove that transformational Leadership, employee commitment and motivation has a positive and significant impact on the job satisfaction either partially or simultaneously and job satisfaction has a positive and significant impact on employee performance.